LC-Q-Orbitrap-MS/MS Characterization, Antioxidant Activity, and α-Glucosidase-Inhibiting Activity With In Silico Analysis of Extract From Clausena Indica (Datz.) Oliv Fruit Pericarps - Wang, Ruimin; He, Ruiping; Li, Zhaohui; Wang, Lu (Frontiers in Nutrition, 2021)
Clausena indica (Datz.) Oliv fruit pericarps (CIOPs) is an important agro-industrial by-products rich in active components. In this article, the effects of traditional and green deep eutectic solvents (DESs) on HPLC characterization, antioxidant activities, and α-glucosidase-inhibitory activity of phenolic extracts from CIOPs were investigated for the first time. Results showed that ChCl-Gly and Bet-CA had higher extraction efficiency for total phenolic content (TPC, 64.14-64.83 mg GAE/g DW) and total flavonoid content (TFC, 47.83-48.11 mg RE/g DW) compared with traditional solvents (water, methanol, and ethyl acetate). LC-Q-Orbitrap-MS/MS was adopted to identify the phenolic compositions of the CIOPs extracts. HPLC-DAD results indicated that arbutin, (-)-e pigallocatechin, chlorogenic acid, procyanidin B1, (+)-catechin and (-)-epicatechin were major components for all extracts, especially for DESs. In addition, ChCl-Xyl and ChCl-Gly extracts showed higher antioxidant activities against 2,2-diphenyl-1-picrylhydrazyl (DPPH•), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS+•), ferric reducing antioxidant power (FRAP), reducing power (RP) and cupric ion reducing antioxidant capacity (CUPRAC) than extracts extracted by other solvents. Strong α-glucosidase-inhibiting activity (IC50, 156.25-291.11 μg/mL) was found in three DESs extracts. Moreover, in silico analysis of major phenolics in the CIOPs extracts was carried out to explore their interactions with α-glucosidase. Multivariate analysis was carried out to determine the key factors affecting antioxidant activity and α-glucosidase-inhibiting activity. In a short, DES can be taken as a promising solvent for valorization and recovery of bio-active compounds from agro-industrial by-products. The results verified that CIOPs can be used as a prospective source rich in bio-active compounds applied in food and pharmacy industries.